2014
DOI: 10.1016/j.juro.2014.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging during Urodynamic Testing Identifies Brain Structures Initiating Micturition

Abstract: Purpose Normal voiding in neurologically intact patients is triggered by the release of tonic inhibition from suprapontine centers, allowing the pontine micturition center to trigger the voiding reflex. Supraspinal mechanisms of voluntary voiding in humans are just beginning to be described via functional neuroimaging. We further elucidated brain activity processes during voiding using functional magnetic resonance imaging in normal females to gain better understanding of normal voiding as well as changes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 17 publications
4
78
0
1
Order By: Relevance
“…Control data were provided by records from HC female subjects reported in our previous study. 5 Men were excluded from study to avoid confounding by prostate pathology.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Control data were provided by records from HC female subjects reported in our previous study. 5 Men were excluded from study to avoid confounding by prostate pathology.…”
Section: Methodsmentioning
confidence: 99%
“…2 Positron emission tomography and fMRI neuro-imaging have shown activation of the right dorsal pontine tegmentum, the right inferior frontal gyrus and other regions for motor control during voiding. 3–5 Following the identification of these circuits in healthy individuals, in recent years investigators have started to study patients with LUTS and urological chronic pelvic pain syndrome to better establish a phenotype and understand these complex urological syndromes. 6,7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plusieurs hypothĂš ses sont avancĂ© es, telles que l'action mĂ© canique avec la pression digitale sur le sphincter vĂ© sical ou alors un mĂ© canisme neurologique central avec la dĂ© sactivation concomitante de la zone du « lĂącher prise », nĂ© cessaire Ă  l'orgasme, et situĂ© e dans le cortex fronto-pariĂ© tal [34], et une de celles du contrĂŽ le de la miction [35], situĂ© dans le lobe frontal et adjacente Ă  la premiĂš re. De nouvelles Ă© tudes sont en cours.…”
Section: Resultsunclassified
“…Specifically, functional MRI (fMRI) studies have identified several cortical brain areas are involved in the regulation of micturition (34). Our institution performed a pilot study of brain activity evaluated by fMRI during simultaneous urodynamic testing in 10 healthy female subjects and identified activation of a brain network consisting of regions for motor control, executive function and emotion processing at “initiating of micturition” (35). These functional imaging protocols can be applied to subjects with various urologic pathologies to better elucidate differences in neural control compared to normal subjects.…”
Section: Imagingmentioning
confidence: 99%